Tax measures to combat brain drain: (In) compatibility issues with double tax conventions and a potential way forward - Souza de Man Fernando (Anali Pravnog Fakulteta u Beogradu)
This article analyzes the interaction between domestic tax legislation applied to avoid or combat a brain drain and the OECD and the UN model tax conventions, the two main models used by states in tax treaty negotiations. After it is demonstrated that brain drain taxes are incompatible with the current tax treaty network, the author presents alternatives that could be included in the model tax conventions, and consequently in tax treaties, to establish the compatibility of the measures, as well as a justification for the adoption of these alternatives in tax treaties involving developing countries.